Genomics Reveals Distinct Evolutionary Lineages in Asian Elephants - Jeroen Kappelhof; Emma Diepeveen; Martijn F. L. Derks; Ole Madsen; Rebekah Rogers; Benoit Goossens; Reeta Sharma; Martien A. M. Groenen; Jack J. Windig; Mirte Bosse (Ecology and Evolution)
ABSTRACT This study introduces, for the first time, whole‐genome sequencing (WGS) data from predominantly wild‐born Asian elephants currently housed in European zoos, covering the distribution range of Asian elephants. With this WGS data, we aim to validate the current designation of Asian elephant subspecies and address currently discussed ambiguities about their origin, particularly concerning Bornean and Sri Lankan elephants by analyzing population structure, determining divergence times, and exploring ancient and recent bottlenecks. Understanding the evolutionary history of the Asian elephant subspecies is essential for developing targeted conservation strategies and mitigating risks to their survival. Analysis reveals a clear population structure with relatively recent splits, delineating three distinct genetic clusters: Borneo, Sumatra, and Asian Mainland, with Sri Lanka forming an additional group. We estimated the divergence time between Bornean and Sumatran elephants to be around 170,000 years ago. The divergence of the Sri Lankan elephant from the Mainland is estimated to have occurred around 48,000 years ago, with Sri Lankan elephants predominantly clustering with those from Myanmar, possibly due to historical trade networks. The genome of the Bornean elephant exhibited signatures of severe bottlenecks as recently as 8 and 38 generations ago, further supporting hypotheses of their introduction. Our data reflect the current Asian elephant subspecies designation. Additionally, for the first time, the Sumatra elephant is confirmed as a distinct subspecies with genomic data. Furthermore, the study discusses genetic management strategies for ex‐situ populations, emphasizing the importance of implementing cluster‐specific conservation measures.